Shunt-Series FACTS Devices on Network Constrained Unit Commitment - G.A. M. Hosaini Hajivar; S.S. Mortazavi (International Journal of Applied Power Engineering (IJAPE), 2016)
Shunt-Series FACTS Devices (SSFD) would play an important role in maintaining security and reduce Total Generation Cost (TGC) in the economical operation of power systems. The application of this devices to the AC model of Network-Constrained Unit Commitment (NCUC) for the day ahead scheduling is presented in this paper. The proposed AC model of NCUC with SSFD would include active and reactive power flow constraints which increase the network controllability at normal operation. A general SSFD model is introduced for the reactive power management in NCUC which is based on the reactive power injection model (RPIM). The case studies reveal that power transfer capability and voltage profile of the power system is improved by compensating SSFD. Meanwhile simulation results demonstrate the combined use of these devices to NCUC have a significant impact on maintaining network security,  lower TGC and increase using the maximum capacity of the existing transmission network.